What do we mean by corporate social responsibility? - Moir, Lance (MCB UP Ltd (Emerald), 2001)
There have long been conflicting expectations of the nature of companies’ responsibilities to society. However, for those businesses that do undertake what might be termed “corporate social responsibility”, what is actually socially responsible behaviour as opposed to management of corporate image management or other activity aimed predominantly at business benefits? This article reviews definitions of corporate social responsibility from both practice and the literature and looks at theories to explain why such behaviour takes place. The literature has strong divides between normative or ethical actions and instrumental activities. The article concludes by posing the question of when instrumental activities become business activities rather than largely social responsibility.
Keywords: Corporate strategy; Social accounting; Social responsibility; Stakeholders